Knowledge, attitudes, and practices toward Mpox among laboratory professionals in Zambia: A cross-sectional study - David Chisompola; John Nzobokela; Elijah Chinyante; Nanjela Chidima; Allen Chipipa; Charlotte Nyirenda; Edward Phiri; Lucky Kalyapu; Sepiso K. Masenga (PLoS ONE, 2025)
Introduction Monkeypox (Mpox), caused by the Mpox virus, is an emerging zoonotic disease of global public health significance. In Zambia, limited data exist on laboratory professionals’ (LPs) preparedness to manage and prevent Mpox outbreaks. This study aimed to assess knowledge, attitudes, and practices (KAP) regarding Mpox among LPs in Zambia. Methods A cross-sectional online survey was conducted among 293 LPs across Zambia from April to August 2025. A structured, validated questionnaire assessed socio-demographic data and KAP toward Mpox. Descriptive statistics, chi-square tests, and logistic regression analyses were performed using Stata version 15. Results Of the 293 respondents, 52.2% demonstrated good knowledge, 47.4% had a positive attitude, and 7.5% exhibited good Mpox-related practices. Significant knowledge gaps were observed, including limited awareness of Mpox transmission (62.5%), complications (76.1%). Additionally, 72% of LPs expressed willingness or support for mandatory Mpox vaccination. LPs working in health centres/clinics (AOR = 0.07; 95% CI: 0.009–0.54; p = 0.11), private hospitals (AOR = 0.05; 95% CI: 0.003–0.74; p = 0.030), public hospitals (AOR = 0.06; 95% CI: 0.011–0.39; p = 0.003), and research or academic institutions (AOR = 0.10; 95% CI: 0.01–0.77; p = 0.027) were significantly less likely to report good Mpox-related practices compared to those working in district or provincial health offices. Conclusion The study highlights a low knowledge, a relatively low positive attitude, and poor practices toward Mpox among Zambian LPs. Identified gaps underscore the important need for targeted education and capacity-building initiatives to enhance Mpox preparedness and response.